2015
DOI: 10.1590/1678-6937
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rumen fermentation kinetics of diets containing oldman saltbush hay and forage cactus, using a cattle inoculum

Abstract: In vitro rumen fermentation kinetics of diets containing oldman saltbush hay and forage cactus, using a cattle inoculum [ ABSTRACTThe aim of this experiment was to evaluate, by means of the semi-automated in vitro gas production technique, fermentation kinetics of carbohydrates and degradability of dry matter (DM) and organic matter (OM) of diets containing oldman saltbush hay levels (8.4; 18.8; 31.2 and 48.3%) associated to forage cactus in natura. Pressure readings of the gases were done with a pressure tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
(15 reference statements)
2
4
1
Order By: Relevance
“…The opposite occurred with the genotypes Miuda and IS since their greater NFC concentration resulted in a greater amount of fermentable substrate at any time, and consequently contributed positively to increasing IVDMD, B and c . These results are in agreement with other studies, where c for spineless cactus ranged from 0.06 to 0.3/h (Abidi et al , 2009; Luz et al , 2014; Tosto et al , 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The opposite occurred with the genotypes Miuda and IS since their greater NFC concentration resulted in a greater amount of fermentable substrate at any time, and consequently contributed positively to increasing IVDMD, B and c . These results are in agreement with other studies, where c for spineless cactus ranged from 0.06 to 0.3/h (Abidi et al , 2009; Luz et al , 2014; Tosto et al , 2015).…”
Section: Discussionsupporting
confidence: 93%
“…This is probably related to the low ADF concentration observed in all genotypes. In agreement with the current results, Batista et al (2003 b ) and Tosto et al (2015) reported Vf 1 of 195–222 ml for different spineless cactus. High gas production and DM degradation of cacti are likely due to their high non-structural carbohydrate and low lignin concentrations, which probably explains the high degradation rate of the slowly degradable DM fraction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With the increase of the NDF content, there is a decrease in the rate of degradation of DM (Figure 1) due to the difficulty of the rupture of these molecules by the bacteria, which affects, mainly, the rate of degradation. In general, this also affects the rate of passage of the feed because, the lower the rate of degradation, the longer the dwell feed retention time in the rumen, (MUNIZ et al, 2012;TOSTO et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The high degradability of cactus organic matter (Tosto et al 2015;Siqueira et al 2017), which comprised 35% of DM of the TH and SB diets, may have increased the synthesis of organic acids (Lins et al 2016) and microbial protein in the rumen of the sheep, which explains the greater gain in weight. In a recent review, Boval et al (2015) verified that the weight gain increases as the digestible dry matter intake increases too.…”
Section: Discussionmentioning
confidence: 99%